The Dynamics of Indonesia’s Sharia Capital Market Development 2014–2024: Opportunities, Challenges, and Strategic Futures - Siti Umi Nurbaidah; Rahmat Hidayat; Desmadi Saharuddin (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The Indonesian Islamic capital market has experienced significant growth over the past decade, both in terms of the number of Islamic stocks, market capitalisation, and increased investor participation. However, its contribution to the total national capital market remains limited. This study aims to comprehensively examine the dynamics of the development of Indonesia's Islamic capital market from 2014 to 2024 through a SWOT analysis approach and the principles of Islamic maqāṣid. The methodology used is a descriptive-qualitative approach based on literature review and secondary data analysis from the OJK, IDX, and relevant empirical sources. The findings indicate that the Islamic capital market has strengths in terms of ethical values and Islamic compliance, but faces structural challenges such as low literacy and liquidity. Strategic opportunities arise from the integration of Islamic fintech, the development of ESG products, and synergy with the national halal economy. This study contributes to the development of maqāṣid-based policies that not only pursue profitability but also ensure sustainability and socio-economic justice.